Envisioning family : a photographer's guide to making meaningful portraits of the modern family - Lackey, Tamara (Voices that matter., 2012)
FAMILY - A small word with powerful meaning. Most of us trace the roots of our own personal identity back to our experience of being part of a family. The definition of what a family is can vary widely, but most family photography is anything but varied. We are used to the basic posing of a group, assembled and smiling like they never do in real life. This doesn't offer much visual or emotional impact. Create an image that captures the spirit of a family - as well as the individualism of the members - and you start at a magical place. That family now feels something when they view the photograph. In Tamara Lackey's Envisioning Family: A photographer's guide to making meaningful portraits of the modern family, Lackey reinvents the family photo for photographers. A top portrait photographer and sought-after speaker, Lackey reveals her techniques for getting each member of the family to feel at home in front of the camera - whether they're in her studio, at home, or on location. With this book you'll learn how to use backgrounds that complement your subjects, set up and shoot in-studio, light your images anywhere with straightforward lighting setups and diagrams, pose your subjects in a beautiful but natural way, nail your exposure, and create meaningful family portraits that leave everyone feeling and looking their honest best. For professional portrait photographers looking to inject some new vitality into their work or aspiring family photographers who would like to take more authentic images, this guide will help capture the modern family.